PENGEMBANGAN MULTIMEDIA PEMBELAJARAN INTERAKTIF TERINTEGRASI AUGMENTED REALITY PADA MATERI PERUBAHAN PERMUKAAN BUMI KELAS V SD - Zulaikha; Ali Ismail; Regina Lichteria Panjaitan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The development of interactive learning multimedia integrated with Augmented Reality is driven by the fact that technology-based learning media are not used enough in IPAS education, especially on abstract materials such as the changes in the earth's surface due to natural factors. This study aims to determine the development procedures, feasibility, effectiveness, and responses of teachers and students to interactive learning multimedia integrated with Augmented Reality on the material of changes in the earth's surface due to natural factors in fifth-grade elementary school. The research design uses a One Group Pretest-Posttest. The Research and Development study uses the ADDIE model, which has five steps: analysis, design, development, implementation, and evaluation. The feasibility test method uses a questionnaire evaluated by expert validators in content and media. Data analysis techniques used include normality tests, hypothesis tests, and N-Gain tests. The effectiveness test of using interactive learning multimedia showed that in the normality test, the pretest result was sig 0.002 < 0.05 and the posttest result was sig < 0.001 < 0.05 (not normally distributed). The hypothesis test (Wilcoxon) yielded a sig (2-tailed) value of < 0.001 < 0.05, indicating a significant difference between the pretest and posttest. The results of the N-Gain test showed an average (mean) of 0.5708 (moderate criteria), and the N-Gain percentage was 57.0839% (fairly effective).